AI Integration in Learning: Case Study of Indonesian Language and Literature Education Students at a Private University in Indonesia - Rosmilan Pulungan; Lisa Septia Dewi Br.Ginting; Elia Putri (STAI Hubbulwathan Duri, 2025)
This study investigates the integration of Artificial Intelligence (AI) in Indonesian Language and Literature Education at Universitas Muslim Nusantara (UMN) Al-Washliyah. AI is increasingly recognized as a transformative tool for enhancing student engagement, language proficiency, and pedagogical innovation. However, its application in the context of Bahasa Indonesia and local literature remains underexplored. Using a qualitative case study design complemented by quantitative survey data, the study involved 50 undergraduate students and 5 faculty members. Data collection methods included classroom observations, student and faculty interviews, focus group discussions, and Likert-scale surveys measuring student motivation, comprehension, and learning experiences. Findings show that AI tools—particularly those utilizing Natural Language Processing (NLP)—significantly improved students’ grammar accuracy, sentence clarity, vocabulary diversity, and reading comprehension. Real-time feedback and adaptive learning features increased motivation and participation by 25–30%. AI also facilitated deeper engagement with regional dialects and literary texts. However, challenges emerged, including limited infrastructure, insufficient AI literacy among faculty and students, and the lack of NLP models optimized for the Indonesian language. The study concludes that AI integration holds significant promise for language and literature education, provided that institutional support, localized AI tools, and training programs are in place. Future research should focus on developing culturally inclusive, linguistically accurate AI systems tailored to low-resource languages.